Transparent computer : designing understandable intelligent systems - Mueller, Erik T. ([Place of publication not identifed] : Erik T. Mueller, 2016)
This book discusses techniques for designing and building transparent compuers ranging from declarative methods to neural networks. It describes ways of implementing dialogue, explanation, and learning in ransparent computers.
Methods for Transparency -- Aspects of Transparency
Includes bibliographical references and index.
Keywords: INFORMATION SYSTEMS